Clinical Depression in Alcohol Dependent Patients in a Tertiary Care Center in the Western Region of Nepal: A Cross-Sectional Study (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Alcohol dependence syndrome (ADS) is one of the common diagnoses in the psychiatry department. ADS is associated with various comorbid psychiatric disorders. We aim to study the prevalence of co-morbid depression in ADS patients.Methods & Materials: We conducted a tertiary hospital-based cross-sectional study using a convenient sampling method. Ethical approval was obtained from the Institutional Review Committee (IRC) of Lumbini Medical College and Teach- ing Hospital (LMCTH). A total of 58 ADS patients were diagnosed using the International Classification of Diseases (ICD)-10 Classification of Mental and Behavioral Disorders. The study duration was 1 year from January 2023 to December. We used the Beck Depression Inventory (BDI) to evaluate depressive symptoms and the Alcohol Use Disorder Identification Test (AUDIT) to assess the severity of drinking in all patients.Results: We found that out of the total 58 ADS patients, 55.17 % were suffering from depressive disorder. More depressive symptoms were observed among depressed ADS than non-depressed ADS patients, which was significant at p-value (0.001*). Also, a significant number of depressed ADS patients (37.5 %) were having suicidal ideation, which was significant at p-value (0.006*). Again, BDI and AUDIT scores correlated at p-value (0.039*). However, depressive symptoms were not associated with gender, age, marital status, family type, locality, socio-economic status, and total AUDIT score.Conclusion: This study showed high estimates of depressive symptoms among ADS patients and high suicidal ideation in depressed ADS patients. So, depressive symptoms should be looked for carefully to detect and treat in ADS patients.